The Pan-European Population Distribution Across Consistently Defined Functional Urban Areas - Kurt Schmidheiny; Jens Suedekum (Institute for the Study of Labor (IZA), 2015)
We analyze the first data set on consistently defined functional urban areas in Europe and compare the European to the US urban system. City sizes in Europe do not follow a power law: the largest cities are "too small" to follow Zipf's law.
Keywords: R11; R12; 330; functional urban areas; Zipf's law; city size distributions; urban systems